Leukocyte immunoglobulin‐like receptor B1 and B4 (LILRB1 and LILRB4): Highly sensitive and specific markers of acute myeloid leukemia with monocytic differentiation. Issue 4 (12th September 2020) - Churchill, Hywyn R. O.; Fuda, Franklin S.; Xu, Jing; Deng, Mi; Zhang, Cheng Cheng; An, Zhiqiang; Zhang, Ningyan; Chen, Pu; Bergstrom, Colin; Kansagra, Ankit; Collins, Robert; John, Samuel; et al.
Abstract: Background: Acute myeloid leukemia (AML) with monocytic differentiation (M‐AML) remains a diagnostic challenge largely due to lack of sensitive and specific markers for immature monocytes. The immunoglobulin‐like inhibitory receptors, LILRB1 and LILRB4, are expressed on monocytes but have not yet been systematically evaluated in the clinical setting. Methods: We evaluated the diagnostic performance of LILRB1 and LILRB4 as monocytic markers for both immature and mature monocytes in comparison to other myelomonocytic markers including CD14, CD15, CD33, CD36, and CD64 in eight cases of control bone marrow (BM, 5) and peripheral blood (PB, 3), 64 cases of (M‐AML), and 57 cases of AML without monocytic differentiation (NM‐AML) by flow cytometric immunophenotyping. Results: In control BM, LILRB1 and LILRB4 were consistently expressed on monocytes at all stages of maturation, from CD34 + /CD14 − monocytic precursors to CD14 −/dim+ maturing and CD14 + mature monocytes. In M‐AML, LILRB1 and LILRB4 were consistently expressed on monocytes, regardless of the degree of maturity, from CD14 −/dim+ monoblasts/promonocytes to CD14 + mature monocytes but were not expressed on myeloblasts. The diagnostic performances as a monocytic marker assessed by sensitivity/specificity were 100%/100% for LILRB1/LILRB4, 100%/82% for CD11b, 80%/100% for CD14, 100%/81% for CD64, 100%/58% for CD15/CD33, and 89%/97% for CD36/CD64. Conclusion: The co‐expression of LILRB1/LILRB4 outperformed other myelomonocytic markers as a highly sensitive and specific marker for monocytes at all stages of maturation and could reliably distinguish M‐AML from NM‐AML. LILRB4 additionally represents a novel therapeutic target for treating M‐AML.